(untitled) (MAUSAM, 1991)
The three dimensional circulation and thermal anomaly features associated with droughts and floods India are examined using 20 year of upper wind data over India and neighbourhood. The analysis reveals that years of droughts (floods) in India are associated with cyclonic (anticyclonic) circulation anomalies and cold (warm) thermal anomalies in the troposphere between 500 hPa and 200 hPa over northwestern India. In drought years (flood years) upper tropospheric westerly (easterly) anomalies are observed in the lower latitudes in the months of May and June. Tibetan anticyclone shifted to east of its normal position in drought years , during the month of June. The correlation coefficient between the meridional component of the wind at 200 hPa over northwestern India and the summer monsoon rainfall found to be -0.72 which is significant.